Case Report: Recurrent Hemiplegic Migraine Attacks Accompanied by Intractable Hypomagnesemia Due to a de novo TRPM7 Gene Variant - Lei, Meifang; Wang, Ping; Li, Hong; Liu, Xiaojun; Shu, Jianbo; Zhang, Qianqian; Cai, Chunquan; Li, Dong; Zhang, Yuqin (Frontiers in Pediatrics, 2022)
Transient receptor potential melastatin 7 (TRPM7) is a ubiquitously expressed chanzyme comprised of a divalent cation channel permeable to calcium and magnesium and a cytosolic serine-threonine α-kinase domain. TRPM7 has a crucial role in magnesium ion homeostasis and anoxic neuronal death, which was identified as a potential non-glutamate target for hypoxic-ischemic neuronal injury. TRPM7 is implicated in ischemic stroke and hypomagnesemia in many studies, but it has not been associated with disease in the OMIM database. No clinical cases between TRPM7 gene variants and hypomagnesemia have been reported, so far. One patient with recurrent hemiplegic migraine attacks accompanied by intractable hypomagnesemia was followed up at Tianjin Children’s Hospital from 2018 to 2021. We systematically summarized and analyzed the clinical manifestations, imaging features, and serum magnesium changes of the patient. Genetic analysis was performed by whole-exome sequencing and Sanger sequencing to infer the etiology of hemiplegic migraine attacks and hypomagnesemia in this patient. Gene sequencing revealed a novel heterozygous variant of the TRPM7 gene (c.2998A>G, p. Met1000Val), which has not been reported previously; this is also a de novo variant that is not inherited from his parents. We described a novel variant p. Met1000Val (c.2998A>G) located in the transmembrane region of TRPM7 protein, which is possibly crucial for the normal function of the ion channel. Our study expands the variation spectrum of the TRPM7 gene, highlights the importance of molecular genetic evaluation in patients with TRPM7 gene deficiency, and demonstrates the causal relationship between TRPM7 gene variants and disease manifestations.